Monitoring of livestock health and production in sub-Saharan Africa - Leeuw, P.N. de; McDermott, John J.; Lebbie, S.H.B. (Elsevier, 1995)
We begin by stressing that relevant and adequate information is an essential ingredient of efficient decision-making processes aimed at optimising the performance of livestock enterprises. Such decisions are universally made, so that though different approaches may be required, animal health and production monitoring (HPM) is as important in sub-Saharan Africa (SSA) as it is in livestock systems in other parts of the world. To set the scene for our discussion of HPM in SSA, we broadly describe the main African production systems in tabular form, categorised by ecological conditions, production goals and input and output relations within a broad farming systems context. Subsequently, the scope and diversity of HPM in SSA is reviewed. This review reveals that in 2 decades of system monitoring, a wide variety of objectives have been tackled from broad system description and constraint diagnosis to more focused research to identify and quantify the impact of disease and other specific factors on the productivity of cattle and small ruminants. There have been many monitoring clients, ranging from national governments through aid agencies and the scientific community, to individual farmers. To serve these diverse clients and their objectives, a plethora of methods and data collection techniques have evolved, monitoring needs of two contrasting production systems (pastoralists in the arid and semi-arid zones and smallholder dairy farmers in the highlands of East Africa) to indicate how monitoring has contributed to our understanding of these systems and how monitoring might be better targeted to satisfy future needs. The impact of HPM on the `state of the knowledge' of traditional African production systems are then summarised at two levels. The first includes specific health and productivity information gained while the second considers the more general lessons learned with respect to livestock enterprise functions and their impact on human welfare. Finally, future monitoring needs are discussed relative to changes in African livestock systems. It is anticipated that further specialisation and intensification of livestock enterprises will require decision-support systems, many of which already exist in the developed world and could be adapted to SSA.